Implementing Cost-effective 3-Dimensional Ultrasound Using Visual Probe Localization - Ali, Aziah; Logeswaran, Rajasvaran (SPRINGER, 2007)
This article proposes a set-up for a 3-dimensional ultrasound system using visual probe localization on the conventional 2-dimensional ultrasound machines readily available in most hospitals. A calibrated digital camera is used for probe-tracking (localization) purposes, whereas ultrasound probe calibration is implemented using a purpose-built phantom. The calibration steps and results are detailed here. The overall system is proven effective in clinical trials through scanning of human organs. Results obtained show successful, accurate 3-dimensional representations using this simple cost-effective set-up.